1998
DOI: 10.1016/s1059-1311(05)80004-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-epileptic attack disorder and clinical outcome: a pilot study

Abstract: Of the total population admitted over a 12-month period to a tertiary referral epilepsy centre for assessment of their seizure disorder, a high percentage were diagnosed with non-epileptic attack disorder. A retrospective analysis of these patients revealed that although intensive therapy and support was offered during the period of admission, the long-term resources for further management post-discharge were inadequate and in some cases non-existent. The implications for patient satisfaction with the service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Of the studies with over 50% seizure remission, three contained paediatric cases only [5–7] and one had a relatively short followup period of two weeks [8]. Riaz and colleagues found that the majority of patients with PNES (67%) had a good outcome [9], but this was defined as either seizure cessation or greater-than-50% reduction in seizure frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies with over 50% seizure remission, three contained paediatric cases only [5–7] and one had a relatively short followup period of two weeks [8]. Riaz and colleagues found that the majority of patients with PNES (67%) had a good outcome [9], but this was defined as either seizure cessation or greater-than-50% reduction in seizure frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Following diagnosis, their feelings about care were neutral or negative. At one year follow-up, however, satisfaction was more positive 23 .…”
Section: Resultsmentioning
confidence: 91%
“…In general, NEAD has a good prognosis. Riaz et al 12 showed that over an 8 week follow-up 25% of NEAD patients were seizure-free following psychiatric treatment, 50% were improved and 25% worse or unchanged. Over a longer followup, the improvement may be even more marked.…”
Section: Discussionmentioning
confidence: 99%